Archaeology, mainly polish, in the current discussion on the ethnogenesis of the Slavs - Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2022)
This paper is an attempt at outlining the current state of discussion about the ethnogenesis of the Slavs, mainly within the framework of Polish scientific research, with particular consideration of archaeological theories, both in terms of their differences as well as any similarities. The discussion covers the allochthonic theory (which is predominant in the science), autochthonic theory, as well as the concept defined by an American archaeologist, Florin Curta, which falls outside these two main discourses. The rationale proposed within this paper could support the resumption of a harmonious discussion among the archaeologists on the problem of the ethnogenesis of the Slavs.